EXPLORING ENGLISH NEEDS OF ENGINEERING STUDENTS IN A VOCATIONAL HIGHER EDUCATION INSTITUTION: A NEED ANALYSIS - Maria Puspa Sari; Zuliana Lestari (Language and Education Journal, 2025)
Need analysis is an initial step in designing a course. At this stage, what students really need to learn is investigated and analyzed so that the course can be well-designed and planned. This study aimed to investigate (1) what language skills, (2) what vocabulary topics, (3) what structures, and (4) what method of learning were needed in the English course in the coal mining engineering department. A triangulation method is used to obtain a comprehensive description of what mining engineering students’ English needs are. The current students, content lecturers, and professionals are the participants of this research. The instruments are a questionnaire (for students), a focus group discussion (for lecturers), and an interview (for professionals). This quantitative-qualitative study uses a descriptive approach in presenting its findings. Based on findings, four English skills should be integrated; the implementation of the four skills and glossary in context should be in line with its area of expertise, the structure of English should be given at the basic level, and L1 should be involved as the medium of instruction.